Muslim Women's Religious Self-Representation on Social Media: A Systematic Review - Ariani Himalia Putri; Desi Dwi Prianti (INJECT (Interdisciplinary Journal of Communication), 2026)
This systematic literature review examines how Muslim women's religious self-representation is conceptualized across social media studies. Employing the SPIDER framework and PRISMA 2020 guidelines, the study synthesized 35 Scopus-indexed peer-reviewed articles published between 2016 and June 2026. Data were analyzed through thematic synthesis and structured coding covering visual religious identity (VRI), self-presentation, platform context, and theoretical framing. The analysis identified five thematic clusters: (1) hijab, modest fashion, and visual aesthetics; (2) religious identity negotiation and digital self-presentation; (3) influencers, branding, activism, and self-representation; (4) platform and community studies; and (5) contextual and cross-platform studies. Findings demonstrate that Muslim women's visual religious identity is not a fixed expression of religiosity, but a contextual representational practice negotiated through visual signs, platform affordances, audience expectations, and moral evaluation. Although self-presentation appeared in 32 of 35 studies, VRI was explicitly central in only 17 studies, revealing a significant conceptual gap. The review further identifies an underexplored area concerning dual-account practices and post-pesantren Muslim women's digital identity. These findings extend Hall's theory of representation into platformed digital religion contexts and suggest directions for future empirical research.